The Effects of Dimensions of Organizational Structure on Innovation in Business School Libraries in India: An Empirical Study - Mishra, Champeswar; Maharana, Bulu (Journal of Information and Knowledge, 2019)
Purpose: In an intensely competitive and changing environment, innovation can be considered as a survival strategy. The purpose of this paper is to investigate the effects of organization structure on innovation in business school libraries in India. Design/methodology/approach: The study focused on libraries of leading business schools, viz., IIMs,. A structured questionnaire was used to collect data for this study. The quantitative data were analyzed to test the hypothesis. Findings: The dimensions of organizational structure i.e., vertical complexity, employee participation and organizational complexity are positively related to innovation and have higher OS influence in innovation among business school libraries. On the other hand, increase in formalization, the degree of centralization and strict adherence to pre-defined roles and rigid rules in the organization are negatively related to innovation. Research Limitations: The study is limited to libraries of Indian Institutes of Management (IIM) India. Thus, other scientific and technical libraries are not in the ambit of this study. Originality/value: In India, there is no study conducted in academic management libraries. This study can be used as a guide for library administrators to accomplish the objectives of the organization by enabling innovation in the context of organizational structure.